Estudo do impacto sonoro no uso de drone em campo livre - Silva, Kadu Gibran (Universidade Federal de São Carlos, 2022)
In recent years there has been an increase in the use of RPAs (remotely piloted aircraft system), for different functions. However, this growth comes with a concern with questions about noise pollution and its possible impacts generated by the drones. To regulate the use of RPAs, which would determine noise limits for the category, it is necessary to carry out studies to identify their characteristics of the emission such as directionality, presence of tonal noise and global noise level. In this work, we present the main methods and standards for sound characterization from a test with a commercial RPA in order to identify possible critical points in the discussion.
Study of noise impact in the use of drones in free field
Keywords: VANTs; Nível global de ruído; Acústica; Emissão de ruído; RPAs; Noise emission; Acoustic; CIENCIAS EXATAS E DA TERRA::FISICA::AREAS CLASSICAS DE FENOMENOLOGIA E SUAS APLICACOES::ACUSTICA